PENGARUH LIKUIDITAS TERHADAP PROFITABILITAS PADA PT. HERO SUPERMARKET TBK YANG TERDAFTAR DI BEI PERIODE TAHUN 2011-2019 - Dewi Silvia (Jurnal Akuntansi dan Keuangan, 2019)
The study aims to examine the effect of the independent variable liquidity ratio (current ratio, quick ratio, and cash turn over ratio) on the dependent variable profitability (ROA). Design descriptive quantitative research with time series analysis methods. The sample selection method use simple random sampling. Partial test results prove that (1) the current ratio does not affect profitability (ROA), (2) quick ratio does not affect profitability (ROA),(3) cash ratio does not affect profitability (ROA). The results of calculations simultaneously prove the Adjusted R Square value of 0.057 or 5.7% the dependent variable is influenced by the three independent variables While the rest is influenced by other factors outside the model. This proves that the company's ability to pay off short-term obligations does not affect the ability to generate profits.